Simulium (Gomphostilbia) taitungense, a new species of black fly (Diptera: Simuliidae) from Taiwan, with description of the male of Simulium (Gomphostilbia) tuenense Takaoka - Huang, Yao-Te; Takaoka, H.; Otsuka, Y.; Aoki, C. (2011)
Simulium (Gomphostilbia) taitungense sp. nov. is described on the basis of reared adult, pupal and mature larval specimens collected from Taitung, Taiwan. This new species is placed in the ceylonicum species-group within the subgenus Gomphostilbia and is distinguished from related known species by the characteristic colour markings on the ventral surface of the head capsule and on the dorsal surface of the abdomen in the larva. The male of Simulium (Gomphostilbia) tuenense Takaoka, which was originally described from a pharate pupa and a larva, is described for the first time; the association of the adult stage with the larval stage was confirmed by the comparison of the sequences of the mitochondrial 16S rRNA gene; this species is also placed in the ceylonicum species-group.